Giving Depth to TEI-Based Descriptions of Manuscripts: The Golden Gospel of Ham - Valieva, Nafisa; Liuzzo, Pietro Maria (Aethiopica, 2021)
The work on the Golden Gospel of Dabra Libānos za-Ham in Eritrea, one of the main archives of the medieval history of Ethiopia and Eritrea, was initiated within the frame of the Ethiopian Manuscript Archives project, ANR EthioChristProcess, and Beta maṣāḥǝft. The work aims to describe the codicological disposition of the archival notes (i.e. arrangement of texts within the codex and its by-side folia), to provide their transcription, translation, and indexation. This article will discuss the encoding method for this work in progress, supported by TEI.